Successful treatment of diffuse alveolar hemorrhage secondary to Mycoplasma pneumoniae complicated with hemophagocytic lymphohistiocytosis in children: a case report and non-systematic literature review - Yang, Min; Liu, Zhong-Qiang; Wang, Yang; Luo, Li-Li; Qiao, Li-Na (Frontiers in Pediatrics, 2024)
Background After quarantine-related measures were completely lifted in China, the respiratory infection rate of children caused by Mycoplasma pneumoniae (MP) increased significantly, and MP infection may lead to rare severe intra- and extrapulmonary manifestation. Hemophagocytic lymphohistiocytosis (HLH) and diffuse alveolar hemorrhage (DAH) are life-threatening clinical syndromes. Timely recognition may contribute to timely treatment and an improved prognosis. Currently there are no reports of children with DAH secondary to MP infection complicated with HLH. Case presentation We successfully treated a previously healthy school-aged child who was admitted to the pediatric intensive care unit with fever, cough, drowsiness, and progressive dyspnea. HLH was confirmed by clinical and testing criteria, DAH was indicated by computed tomography scan of the chest, and Mycoplasma antibody detection and endotracheal aspirates pathogen metagenomic next-generation sequencing (mNGS) confirmed MP infection. After invasive mechanical ventilation, antibiotics, and glucocorticoid treatment, the patient recovered well and was discharged. At follow-up, she did not experience any more initial symptoms. For the fourth consecutive month, all indexes remained normal. Conclusion mNGS can be considered for identifying the causative agent of infection in patients with DAH and/or HLH. The clinical manifestations of DAH in children may only present as acute hypoxic respiratory failure, significantly decreased hemoglobin without bleeding elsewhere, and chest imaging findings may assist in the diagnosis of DAH. When MP infection is associated with hemocytopenia, HLH should be considered.